DEVELOPMENT OF INTERNATIONAL COOPERATION IN PRIVATE HIGHER EDUCATION INSTITUTIONS (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The process of globalization creates a need for a new level of professional personnel. Currently, the solution to this problem is related to the internationalization of education. A key component of the internationalization process is academic mobility. The main forms and directions of international cooperation between universities of different countries are similar. Today, private universities in our country should establish cooperation with internationally prestigious institutions of higher education and strengthen the exchange of experience.